2015
DOI: 10.5505/tjtes.2015.33848
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caffeic Acid Phenethyl Ester on Inflammatory Cytokines after Acute Spinal Cord Injury

Abstract: BACKGROUND:The purpose of this study was to investigate the effects of Caffeic Acid Phenethyl Ester (CAPE) on proinflammatory cytokines, IL-1β and TNF-α, and explore its healing effect after acute spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…At present, the NF-κB pathway has been most extensively studied. However, the inflammatory pathway is a multi-channel reticular structure (18), as a result, it is not determined by a certain pathway. The mechanism underlying inflammation will become increasingly clear with research on each pathway, and the reticular structure of the inflammatory pathway will be elucidated (19); therefore, it will be more easily controlled.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the NF-κB pathway has been most extensively studied. However, the inflammatory pathway is a multi-channel reticular structure (18), as a result, it is not determined by a certain pathway. The mechanism underlying inflammation will become increasingly clear with research on each pathway, and the reticular structure of the inflammatory pathway will be elucidated (19); therefore, it will be more easily controlled.…”
Section: Discussionmentioning
confidence: 99%
“…This impairment is at least partially mediated by the release of pro‐inflammatory cytokines. These cytokines will induce cellular apoptosis, axonal destruction and extensive demyelination during secondary spinal cord injury .…”
Section: Introductionmentioning
confidence: 99%
“…with a proportion >20-50% (23). Although pre-hospital first aid and clinical therapy has received continuous innovation and improvement, early mortality from acute SCI caused by respiratory failure remains at a high level (23). The results of the present study indicated that sparstolonin B significantly recovered the decrease in BBB score and the increase in the water content of the spinal cord in SCI rat.…”
Section: Discussionmentioning
confidence: 55%
“…with a proportion >20-50% (23). Although pre-hospital first aid and clinical therapy has received continuous innovation and improvement, early mortality from acute SCI caused by respiratory failure remains at a high level (23).…”
Section: Discussionmentioning
confidence: 99%